(untitled) (Research, Society and Development, 2021)
The indices of water quality (IQA) and bathing conditions (ICB), associated with environmental perception, can designate the relationship between man and the aquatic environment. The objective of this research was to analyze the water quality and bathing conditions of the Ipixuna River, in Ipixuna do Pará. The method used was quantitative and qualitative. For the IQA: two samples were collected in two periods (dry and rainy); for ICB, 25 water samples were collected in five different points, during five consecutive weeks. The data obtained and analysis indicated that the IQA presented very few variables in disagreement with what is contained in the CONAMA Resolution 357/05 as, for example, pH ( 5,54); Ptotal ( 0.1 mg/L) and Ntotal (1,58 mg/L), however they did not compromise its quality; In relation to the ICB, the analysis of the data obtained indicated that all sampling points presented improper classification for bathing with the need for suspension of use through temporary signaling, daily water sampling and identification of the source of contamination. Regarding the values of E. coli, they were between 50>500 CFU/100 mL in all sampling points studied, therefore, water with subcategories "excellent", "very good" and "satisfactory". Regarding environmental perception, almost half (n = 49; 44.54%) of the sampled individuals said that the water quality was bad; the others (n = 54; 49.08%) felt some discomfort: skin and eye irritation after bathing. Therefore, control of the water quality of the Ipixuna River should be carried out at least every semester to ensure the well-being of the population of the municipality and the environmental quality.